2012
DOI: 10.3109/09513590.2012.705393
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and endocrine outcome after robot-assisted laparoscopic myomectomy (RALM)

Abstract: RALM seems to have a favorable impact on the reproductive outcome of young patients with no impact on the ovarian function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 25 publications
6
31
0
Order By: Relevance
“…In this study, the mean number of removed myomas for each case was 3.8 ± 3.5 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This is greater than the values in other studies (4,7,8,11,12). In general, the more myomas are resected, the greater time required for the surgery.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, the mean number of removed myomas for each case was 3.8 ± 3.5 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This is greater than the values in other studies (4,7,8,11,12). In general, the more myomas are resected, the greater time required for the surgery.…”
Section: Discussionmentioning
confidence: 74%
“…25 A recent Cochrane Systematic Review reported no significant difference in the rate of cesarean section after open and laparoscopic myomectomy (OR 0.59, 95% CI 0.13 to 2.72). 24 The considerably lower rate of cesarean section in our patients may have been influenced by the greater interval of time from the procedure and when they began actively attempting to conceive.…”
Section: Discussionmentioning
confidence: 80%
“…Cela et al reported that 77.8% of subjects desiring pregnancy were able to conceive and maintain a viable pregnancy after undergoing RALM. 24 Lonnerfors and Persson reported that 15 out of 22 (68.2%) women who actively attempted to achieve pregnancy were successful after removal of deep intramural myomas by RALM. 28 Tusheva et al reported a pregnancy rate of 75% in 16 RALM patients desiring pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Endocrinologic evaluation (day 3 follicle stimulating hormone of menstrual cycle and anti-mullerian hormone levels) of young women undergoing RALM have shown preservation of ovarian reserve 6 months after surgery. 61 The largest retrospective study of pregnancy outcomes after RALM in 872 women, found that observed miscarriage rate (19%) was in the range of those reported after LM. 59 Higher preterm delivery rates were significantly associated with greater number of myomas removed and anterior location of the largest incision.…”
mentioning
confidence: 94%